Harmonization Of The Aviation Sector Within President Jokowi’s Maritime Policy:A Way To Promote Pioneer Flights - Nugraha, Ridha Aditya (UI Scholars Hub, 2016)
As the biggest archipelagic state in the world, the Indonesian government has been aware of the importance of both air and sea transportation in connecting the remote islands with the main islands and thus developing the economy. However,it could not be denied that for many years the country had been trapped within a transportation policy favoring land over the aviation and maritime sectors. It thus came as a relief when the current government announced a pro-maritime transportation policy as their main priority. While this pivot is certainly welcome, it still fails to address the other ‘life line’ of the Indonesian geographic periphery, namely aviation. Currently airlines serve pioneer or isolated routes to these areas which are not financially viable, meaning they are flying at a ‘loss’. To compensate this, state subsidies are granted to these airlines. One of the main concerns therefore, is that there must not be an overlap between airline and ship routes so that subsidies can be concentrated to maximize coverage of the remote islands.Harmonization between the aviation and maritime sectors must be translated within a legal framework.Learning from the European Union is one of the best options so far considering their successful law making and effective implementation within its member states to avoid overlapping between airlines and other transportation modes. Furthermore, failure to present subsidies under Public Service Obligation to develop the aviation, not only maritime, sectors shall mean a nightmare for the country's dream to become a maritime axis in ASEAN.